Routine antenatal ultrasound by nurse-midwives in rural Kenya: a pragmatic trial assessing feasibility and effects of the Mimba Yangu (My Pregnancy) project - Hanson, Claudia; Nyaga, Lucy; Leekha, Nidhi; Mantel, Michaela; Kedenge, Sarah; Gitonga, Caroline W.; Naanyu, Violet; Shah, Jasmit; Temmerman, Marleen (Frontiers in Global Women's Health, 2025)
IntroductionTask-sharing of obstetric ultrasound between nurse-midwives and doctors has the potential to operationalize the World Health Organization’s recommendation of at least one ultrasound before 24 weeks of gestational age for every pregnant woman. Here, we report on the feasibility, acceptability, and effects of the Mimba Yangu (My Pregnancy) task-sharing approach in rural Kenya.MethodsWe conducted a pragmatic trial including 28 primary care facilities between April 2021 and March 2022, selected based on feasibility criteria. Fourteen facilities received the ultrasound intervention composed of (i) task-sharing with nurse-midwives, (ii) the use of portable ultrasound devices (Lumify™) connected to a tablet, and (iii) a digital platform facilitating distant support. Hybrid training of 32 nurse-midwives was provided based on a nationally derived curriculum, including theoretical and hands-on components, by an academic team. We used (i) in-depth interviews with nurse-midwives and healthcare managers, (ii) exit interviews using a quantitative questionnaire with pregnant and recently delivered women, and (iii) data abstraction from the health facility records. We descriptively analyzed data and used a difference-in-difference analysis based on a generalized linear model to assess the effect of the intervention on the number of antenatal visits.ResultsThe intervention was successfully and consistently implemented during a 9-month period in all 14 health facilities providing obstetric ultrasound services to 2,799 pregnant women. Interviews with trained nurse-midwives indicated that the intervention was relevant, feasible, and acceptable. In the intervention facilities, 50.4% of pregnant women received at least one ultrasound compared with 19.2% in the comparison facilities, where women were referred to other facilities for an ultrasound based on obstetric risk factors.ConclusionOur analysis provides evidence of the feasibility, acceptance, and positive effects on service availability of providing ultrasound at the primary care level delivered by nurse-midwives. Scalability and feasibility of such an intervention are critical to global health but will demand policy reforms to allow task-sharing at national and sub-national levels.